Julmarichardiidae, a new apseudoidean family (Crustacea: Tanaidacea: Apseudomorpha) with the description of a new species of Julmarichardia Guţu, 1995 from the Northwest Australian Shelf - Moralés-Núñez, Andres G.; Heard, Richard W. (Zootaxa, 2021)
A new tanaidacean family Julmarichardiidae is designated to receive the Indo-Pacific genus Julmarichardia Guţu. The new family is characterized by having a prominent rostrum, a strongly developed coxal process of pereopod-1 with plumose setae and sometimes spines, and the presence of mucus glands and packets throughout its body. The latter appear to be involved in the construction of a mucus domicile. Based on distinctive antennal and pereopodal characters, the South China Sea species, J. bajau Bamber & Sheader, is placed in a new monotypic genus. A second Australian species is described from specimens collected on the northwestern continental shelf from depths of 37 to 83 m. The new species can be distinguished from its sympatric congener J. gutui Ritger & Heard by a variety of characters, including the lack of setulose setae on the rostral margin and the posterior margin of pereopod-1 having three or fewer setulate setae. It differs from J. alinati Guţu, by the shape and/or spination of the rostrum, antennule, and antenna. Julmarichardia dollfusi (Guţu) is removed from Julmarichardia and designated as Metapseudidae incertae sedis. A key to the six species comprising the genus Julmarichardia is presented.